Analysis Of Internal And External Factors In Improving Services In The District Office - Johannes Johny Soetikno; Hasniaty Hasniaty (Universitas Dharma Wacana, 2022)
Analysis of Internal and External Factors in Improving Services at the District Office. This study aims to identify and analyze strategic planning and implementation carried out by at the District Office in improving services to the community. This research was conducted in Tamalatea Subdistrict, Jeneponto Regency. The data analysis technique used in this study was qualitative analysis, namely using the SWOT analysis technique which was used to develop the potential of the organization and to determine the internal and external factors of the organization. In the SWOT analysis that has been carried out in the Manjangloe village, it can be seen that the Manjangloe village is included in the quadrant I strategy which means it supports aggressive strategies, therefore in organizational development that will be achieved has a very large opportunity, so this can be a good development. for the Manjangloe village